Travelog: Hidden Treasures in the Empire of Cotabato Through the Lens of a Filipino Teacher - Perez, Ma. Ana Carla (International Journal of Arts, Sciences and Education, 2025)
Abstract The research titled Travelog: Hidden Treasures in the Empire of Cotabato Through the Lens of a Filipino Teacher aims to examine the reactions of netizens to a travelogue shared on a social media platform, one hour, one day, and one week after its publication. Using the qualitative method of photo-elicitation, the researcher discussed the hidden treasures in the Empire of Cotabato, such as waterfalls, resorts, and other natural landscapes featured in the travelogue, to understand how these were received by netizens. Based on the research results, the travelogue received high ratings in terms of quality, with the expression of ideas achieving the highest mean score of 4.80 (SD=0.40), followed by relevance and content. Overall, the travelogue received a descriptive rating of "Highly Acceptable," with a total mean score of 4.59 (SD=0.56), indicating the high quality of the travelogue's creation. In discussing the reactions of the netizens, the data showed a rapid increase in the number of likes, hearts, shares, views, and comments from one hour, one day, and one week. After one week, the post had garnered 122 likes, 405 hearts, and 13,332 views, indicating continued interest and active participation from the public. These reactions reflect the successful dissemination of information about the hidden treasures in Cotabato and their wide acceptance on social media.